Análise estática de dutos enterrados pelo acoplamento entre o método dos elementos finitos e o método dos elementos de contorno. - Menezes Junior, Raimundo Aprigio de (2012)
This work deals with the analysis of soil-structure interaction modeling of pipeline problems in static behavior using the coupling between Finite Element Method (FEM) and Boundary Element Method (BEM).The representation of the pipe is made by MEF using two finite elements in the cylindrical panel: The first, formulated from the classical theory of cylindrical shells by assumptions of Donnel and initially proposed by Djoudi & Bahai, using the Assumed Strain Based Model. The second formulated from the theory of equivalent discrete layers (Layerwise Theory), proposed by J. N. Reddy. The soil is represented by elastic continum infinite or semi-infinite and modeled using boundary elements with special curved surface, associated with cylindrical panel, used to represent the soil-structure interaction within the soil, especially at the contact surface with the pipe. Besides the mathematical representation of the model, this work propose a library DLL (Dynamic Link Library) written using the object-oriented programming (OOP) for processing soil structure interaction problems and a user-friendly environment built using the ObjectARX library for customizing AutoCAD.